Access to SCN-containing thiazolines via electrochemical regioselective thiocyanothiocyclization of N-allylthioamides. Issue 11 (23rd April 2020) - Zhang, Yan-An; Ding, Zhong; Liu, Peng; Guo, Wei-Si; Wen, Li-Rong; Li, Ming
Abstract : An electrochemical thiocyclization of N -allylthioamides has been developed for the synthesis of SCN-containing 2-thiazolines and NCS-containing thiazines. Abstract : An electrochemical thiocyanothiocyclization of N -allylthioamides has been developed for the synthesis of SCN-containing 2-thiazolines. This method provides a green and efficient approach to generate 5- ex o-cyclization 2-thiazolines with a broad substrate scope and good yields. In addition, 6- endo -cyclization isothiocyanato thiazines are formed regioselectively when cyclic thioamides are used as reactants. The reaction is easy to proceed under catalyst-, additive- and oxidant-free conditions.